Differential expression of aldehyde dehydrogenase 1a1 (ALDH1) in normal ovary and serous ovarian tumors - Penumatsa Krishna; Edassery Seby L; Barua Animesh; Bradaric Michael J; Luborsky Judith L (BMC, 2010)
Abstract Background We showed there are specific ALDH1 autoantibodies in ovarian autoimmune disease and ovarian cancer, suggesting a role for ALDH1 in ovarian pathology. However, there is little information on the ovarian expression of ALDH1. Therefore, we compared ALDH1 expression in normal ovary and benign and malignant ovarian tumors to determine if ALDH1 expression is altered in ovarian cancer. Since there is also recent interest in ALDH1 as a cancer stem cell (CSC) marker, we assessed co-expression of ALDH1 with CSC markers in order to determine if ALDH1 is a potential CSC marker in ovarian cancer. Methods mRNA and protein expression were compared in normal human ovary and serous ovarian tumors using quantitative Reverse-Transcriptase PCR, Western blot (WB) and semi-quantitative immunohistochemistry (IHC). ALDH1 enzyme activity was confirmed in primary ovarian cells by flow cytometry (FC) using ALDEFLUOR assay. Results ALDH1 mRNA expression was significantly reduced (p < 0.01; n = 5) in malignant tumors compared to normal ovaries and benign tumors. The proportion of ALDH1+ cells was significantly lower in malignant tumors (17.1 ± 7.61%; n = 5) compared to normal ovaries (37.4 ± 5.4%; p < 0.01; n = 5) and benign tumors (31.03 ± 6.68%; p < 0.05; n = 5). ALDH1+ cells occurred in the stroma and surface epithelium in normal ovary and benign tumors, although surface epithelial expression varied more in benign tumors. Localization of ALDH1 was heterogeneous in malignant tumor cells and little ALDH1 expression occurred in poorly differentiated malignant tumors. In benign tumors the distribution of ALDH1 had features of both normal ovary and malignant tumors. ALDH1 protein expression assessed by IHC, WB and FC was positively correlated (p < 0.01). ALDH1 did not appear to be co-expressed with the CSC markers CD44, CD117 and CD133 by IHC. Conclusions Total ALDH1 expression is significantly reduced in malignant ovarian tumors while it is relatively unchanged in benign tumors compared to normal ovary. Thus, ALDH1 expression in the ovary does not appear to be similar to breast, lung or colon cancer suggesting possible functional differences in these cancers. Significance These observations suggest that reduced ALDH1 expression is associated with malignant transformation in ovarian cancer and provides a basis for further study of the mechanism of ALDH1 in this process.